CRELD2, endoplasmic reticulum stress, and human diseases - Tang, Qin; Liu, Qinhui; Li, Yanping; Mo, Li; He, Jinhan (Frontiers in Endocrinology, 2023)
CRELD2, a member of the cysteine-rich epidermal growth factor-like domain (CRELD) protein family, is both an endoplasmic reticulum (ER)-resident protein and a secretory factor. The expression and secretion of CRELD2 are dramatically induced by ER stress. CRELD2 is ubiquitously expressed in multiple tissues at different levels, suggesting its crucial and diverse roles in different tissues. Recent studies suggest that CRELD2 is associated with cartilage/bone metabolism homeostasis and pathological conditions involving ER stress such as chronic liver diseases, cardiovascular diseases, kidney diseases, and cancer. Herein, we first summarize ER stress and then critically review recent advances in the knowledge of the characteristics and functions of CRELD2 in various human diseases. Furthermore, we highlight challenges and present future directions to elucidate the roles of CRELD2 in human health and disease.